2001
DOI: 10.1126/science.1057766
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an Initiation Factor Bound to the 30 S Ribosomal Subunit

Abstract: Initiation of translation at the correct position on messenger RNA is essential for accurate protein synthesis. In prokaryotes, this process requires three initiation factors: IF1, IF2, and IF3. Here we report the crystal structure of a complex of IF1 and the 30S ribosomal subunit. Binding of IF1 occludes the ribosomal A site and flips out the functionally important bases A1492 and A1493 from helix 44 of 16S RNA, burying them in pockets in IF1. The binding of IF1 causes long-range changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
375
0
13

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(415 citation statements)
references
References 38 publications
27
375
0
13
Order By: Relevance
“…Upon RRF binding, the tip of the helix 44 goes through a rotation (Ϸ18°) around the axis of the helix and a shift (Ϸ7 Å, Fig. 2c), which are of similar magnitudes as reported previously upon binding of EF-G (26,27) and IF1 (2). The position of the tip of 23S rRNA helix 69 in RRF-bound and unbound maps are significantly different (Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Upon RRF binding, the tip of the helix 44 goes through a rotation (Ϸ18°) around the axis of the helix and a shift (Ϸ7 Å, Fig. 2c), which are of similar magnitudes as reported previously upon binding of EF-G (26,27) and IF1 (2). The position of the tip of 23S rRNA helix 69 in RRF-bound and unbound maps are significantly different (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Translation on the ribosome comprises of four main steps: (i) initiation, (ii) elongation, (iii) termination, and (iv) recycling. Recent advancements in structural studies of the translational machinery have helped elucidate binding positions and functions of various translational factors involved in various stages of initiation (1,2), elongation (3,4), and termination (5-7). The fourth step of translation requires binding of a dedicated protein factor, the ribosome-recycling factor (RRF), which in conjunction with elongation factor G (EF-G) helps removing the mRNA and last deacylated tRNA from the ribosome (see ref.…”
mentioning
confidence: 99%
“…First, in structural models, the A site is seen to be exposed on the surface of the small 30 S subunit [28]. Secondly, unpaired base residues A 1492 and A 1493 within the A site are crucial to the decoding process and to codon/anticodon recognition [4], the selection of tRNA by the ribosome [29], as well as to the binding of initiation factor 1 [30]. Thirdly, the A site is well known to be the site of interaction of aminoglycoside antibiotics [4,31], which can therefore provide tools for assay development and target validation.…”
Section: Resultsmentioning
confidence: 99%
“…It was therefore suggested that IF1 mimics the A-site-bound tRNA and could prevent premature binding of aminoacyl-tRNA by blocking the A-site on the 30S ribosomal subunit [16]. The crystal structure of IF1 bound to the 30S subunit has shown that IF1 indeed occludes the ribosomal A-site and flips out the functionally important bases A1492 and A1493 from helix 44 of 16S RNA, hiding these bases inside IF1 [17]. These latter X-ray data suggest that IF1 binds to the A-site in a different manner than does the A-site-bound tRNA [16,18,19].…”
Section: Introductionmentioning
confidence: 99%